Harnessing pycnidia-forming fungi for eco-friendly nanoparticle production, applications, and limitations - Rai, Mahendra; Zimowska, Beata; Shende, Sudhir S.; de Matos, José Milton Elias; Ingle, Pramod U.; Golińska, Patrycja; Trzcińska-Wencel, Joanna; Gade, Aniket K. (Frontiers in Microbiology, 2025)
Nanotechnology is pivotal in various fields, including medicine, agriculture, environment, and catalysis. The synthesis of nanomaterials, typically within the 1–100 nm range, can be achieved through physical, chemical, and biological methods. Mycosynthesis, a biological approach, involves using fungi for nanoparticle (NP) synthesis. Several members of the order Pycnidial fungi have recently been reassigned to families such as Didymellaceae, Mycosphaerellaceae, Botryosphaeriaceae, and Diaporthaceae. Pycnidial fungi, including Phoma, Phyllosticta, Phomopsis, Macrophomina, and Botryosphaeria, have been reported to mainly synthesize silver and gold NPs, with Phoma being the most extensively studied genus. In the present review, keen attention is given to the mechanism of NP synthesis using different members of pycnidial group. The mechanism proceeds through the preparation of a cell-free extract, followed by its treatment with metal precursor salts in the solution. The synthesis of silver or gold NPs occurs via the process of reduction of metal ions into respective NPs by various secondary metabolites present in the fungal secretions. This review focuses on the role of pycnidial fungi in synthesizing various NPs, explores the underlying mechanisms, and highlights their significant applications in medicine, the environment, industry, and agriculture. The NPs synthesized from pycnidial fungi are multiplexed for various applications like antimicrobial agents, free radical scavengers, hallmarks for DNA disintegration in cancerous cells, as a potential drug delivery system, as a catalyst, and many more. Although several reports document the role of pycnidial fungi in nanoparticle (NP) synthesis, the precise molecular mechanism underlying NP synthesis still needs to be unraveled before considering their commercial use as microbial factories for biogenic NP production. In addition, the critical challenges in NP synthesis by pycnidial fungi are discussed.